Analisis Kinerja Protokol Routing IS-IS dan Protokol Routing EIGRP Pada Jaringan Topologi Mesh - Aidi Rahman; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
In communicating and exchanging information, the internet requires a routing protocol that can help the process of sending data from the source location to the destination location. There are many types of routing protocols used in sending information. Each type of routing protocol has different characteristics and algorithms that can affect the performance of each routing protocol. It is necessary to do this research to find out which routing protocol has the best performance in the mesh topology network. The research was conducted using the GNS3 simulator application to create a mesh topology that is implemented with the IS-IS and EIGRP routing protocols. Mesh topology is divided into 2 forms, namely by using 5 routers and 8 routers which will be tested with a test scenario to determine the performance of each routing protocol based on the parameters used. By comparing the parameters of throughput, packet loss, update routing table, delay and convergence duration, the results show that the topology of 5 routers using a full connected connection shows that IS-IS has a greater throughput value, namely 2319.52 kbps. In routing table updates, IS-IS has a faster update time of 0.059 s. Then in the delay parameter, EIGRP has a smaller average time, namely 0.165 s. In the parameter convergence duration, IS-IS has a faster time, namely 6.6 s. And the packet loss parameter IS-IS has a smaller amount, namely 3.3%. Then on the 8 router topology that uses partially connected connections, it shows that EIGRP has a higher throughput value, namely 367.68 kbps. In the routing table update, EIGPR has a faster update time of 0.186 s. Then in the delay parameter, EIGRP has a smaller average time, namely 0.612 s. In the parameter convergence duration, EIGRP has a faster convergence time of 13.8 s. And the packet loss parameter EIGRP has a smaller amount of packet loss, namely 6.9%.